Video Kartun dan Video Animasi dapat Menurunkan Tingkat Kecemasan Pre Operasi pada Anak Usia Pra Sekolah - Ajeng Dwi Retnani; Titin Sutini; Suhendar Sulaeman (Jurnal Keperawatan Silampari, 2019)
The purpose of this study was to analyze the effect of cartoon videos and animated videos on reducing preoperative anxiety levels in pre-school age children. This research method uses quasi-experimental with a pre and post-test approach with out control. The results showed that the reduction in preoperative anxiety levels in pre-school children after being given a cartoon video intervention by 4.20, after being given an animated video intervention by 4.70 and after being given a combination intervention between cartoon videos + animated videos by 7.20. Based on this, the level of preoperative anxiety using a cartoon video + animated video combination intervention showed the greatest decrease. The results of the study also obtained p value> 0,000. Conclusions, the influence of cartoon videos and animated videos on the reduction of preoperative anxiety levels in pre-school age children. Keywords: Animation, Anxiety, Pre Operation, Cartoon Video